2018
DOI: 10.1177/0040517518792750
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of carbon nanotube- and graphene-glass fiber fabric-reinforced epoxy composites: A comparative study

Abstract: This study was focused on the comparative effect of tube- and sheet-like nanocarbons on the structure–property relationships of fiber-reinforced composites. Graphene nanosheets and multi-walled carbon nanotubes (MWCNTs) were dispersed into commercial glass fiber fabric (Gf) to obtain multiscale graphene-Gf- and MWCNT-Gf-reinforcing materials, respectively, followed by a vacuum-assisted resin infusion process. The influence of MWCNTs and graphene on the mechanical and thermal performance of multiscale composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Recently, Zeng et al. [ 154 ] investigated the effect of the tube‐and sheet‐like nanocarbons modification of GF fabric on the various properties of epoxy‐based composites and explored their reinforcement mechanisms at the fiber/matrix interface. Four different nanocarbons such as pristine MWCNT, carboxyl MWCNT, pristine graphene, and GO were used to manufacture nanocarbon‐GF/epoxy composites.…”
Section: Properties Of Graphene and Cnt Modified Smart Frp Compositesmentioning
confidence: 99%
“…Recently, Zeng et al. [ 154 ] investigated the effect of the tube‐and sheet‐like nanocarbons modification of GF fabric on the various properties of epoxy‐based composites and explored their reinforcement mechanisms at the fiber/matrix interface. Four different nanocarbons such as pristine MWCNT, carboxyl MWCNT, pristine graphene, and GO were used to manufacture nanocarbon‐GF/epoxy composites.…”
Section: Properties Of Graphene and Cnt Modified Smart Frp Compositesmentioning
confidence: 99%
“…During the pull-out test of a single CNT-coated fiber from the polymer matrix, the surface of the fiber is clean and completely devoid of traces of either CNTs or polymer, indicating the failure occurs at the interface between fiber and CNTs (Agnihotri et al, 2011;Agnihotri et al, 2012). Experiments have also revealed that graphene has a better effect on the improvement of interfacial strength than CNTs (Zeng et al, 2018). The combined effect of carbon nanomaterials on the interfacial properties has also been investigated (Hua et al, 2017).…”
Section: Mechanism Of Interfacial Adhesion Caused By Carbon Nanomaterials Coatingmentioning
confidence: 99%
“…It has wide applications in defense, electronics, renewable energy, etc. due to its outstanding physical properties including light weight and high chemical, mechanical, and thermal durability [ 3 , 4 , 5 ]. According to recent studies, the market for fibre-reinforced composites in the USA has reached $12 billion in 2020 with an expected annual growth rate of 6.6% due to its adaptation in many modern applications such as wind energy [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%